Analysis of experience of legal regulation in the sphere of public administration of sanatorium providing of children in the Russian Federation. - Kovalenko, T. Yu. (Medicni Perspektivi, 2014)
Motherhood and childhood are one of the main priorities of the government social policy for any country. The Ukrainian state, its President and government are keeping under scrutiny issues of improving quality of life and health of population, in particular, health of women and children. Continuing study of problems of Public Administration in the sphere of health resort services for children in Ukraine, in her previous scientific publications the author drew attention to insufficient scope of researches and weak grounds of theoretical justification of possible organizational changes in this sphere. This very fact stipulates the necessity to continue thorough scientific research and study, first of all, a positive experience of foreign countries as to implementing reforms in the sphere of health resort services for children. The share of separate factors of different nature, impacting indicators of public health depends on age, sex and individual-typological characteristics of a person. However, the greatest impact on a human health is made by his lifestyle that may be attributed to conditionally controlled process. In this case, it is appropriate to note that the controlled impact on lifestyle can be made both by internal factors (e.g., motivation), and external factors. One of the most powerful external factors of controlled impact on the public health is health resort provision. The experience of the Russian Federation in this area is extremely useful for the Ukrainian state, which is actively promoting the idea of the health system modernization in the domestic market as the area in need of such changes. Now, 1997 health resorts are operating in the Russian Federation, annually serving approximately 6 million people. The jurisdiction of the Ministry of Health and Social Development of the Russian Federation encompasses 51 health resort facilities (HRF) providing a wide range of health-improving services. The laws, government regulations, orders of the Ministry of Health and Social Development of the Russian Federation and regulatory legal acts of the federal authorities are applied with the introduction of principles of the insurance management model of the legal framework components of public administration in the area of health resort services for children in the Russian Federation. The strategic basis for the government policy in the area of health resort services is the Federal Law of the Russian Federation from November 21, 2011 No. 323-ФЗ “On the Basis of Public Health in the Russian Federation”, which content actualized basic government guarantees of health resort services for children. Implementation of directions of development and improvement of health resort care in the Russian Federation has been legitimized through the agreement on co-financing of the government commitment made between the Ministry of Health and Social Development of the Russian Federation as a central executive authority and local executive authorities to implement measures to create a healthy lifestyle.